Altered human neutrophil FcγRI and FcγRIII but not FcγRII expression is associated with the acute coronary event in patients with coronary artery disease. Issue 1 (January 2017) - Zhao, Na; Mi, Lan; Zhang, Yaping; Li, Na; Xu, Jiaojiao; Xia, Dongyu; Wang, Junkui; Wu, Yue; Liu, Xiaojun
Abstract : Objective: Neutrophils enhancing atherosclerotic plaque instability have been observed in patients with acute coronary syndrome (ACS). Generally, activation of neutrophils in lesions depends on the interaction of Fcγ receptors (FcγRs) with immunoglobulin G antibodies in immune complexes. However, altered FcγR expression on neutrophils of patients with ACS is unknown. We aimed to evaluate changes in FcγR expression on neutrophils of patients with ACS. Methods: We enrolled 106 patients who were divided into four groups: acute myocardial infarction (AMI), unstable angina (UA), stable angina, and normal coronary arteries. The expressions of FcγRI, FcγRII, and FcγRIII on neutrophils and related upstream ligand and downstream molecules were measured by flow cytometry and enzyme-linked immunosorbent assay. Results: The expression of unbound FcγRI was significantly decreased in AMI and UA patients and that of unbound FcγRIII was significantly decreased in AMI patients, with no difference in the expression of unbound FcγRII among the four groups. In contrast, plasma levels of antioxidized LDL antibody, myeloperoxidase, matrix metalloproteinase-9, and neutrophil gelatinase-associated lipocalin were significantly greater in AMI and UA than in stable angina and normal coronary arteries patients. Conclusion: Unbound FcγRI and FcγRIII expression was decreased on neutrophils of patients with ACS, which reflects a potential role of disturbed FcγRI and FcγRIII expression in the destabilization of atherosclerotic plaque. Our findings may provide insight into the mechanism underlying culprit plaque-relevant activation of neutrophil FcγRs in ACS patients.